2018
DOI: 10.5688/ajpe6403
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology Inclusion in Pharmaceutical Sciences Education in Portugal

Abstract: Objective. To analyze the inclusion of nanotechnology in the curricula of Integrated Master's in Pharmaceutical Sciences programs in Portugal. Methods. Information regarding curricula (general notice and curricular unit description, objectives and syllabus) from national institutions was collected from their official websites or requested by e-mail, and analyzed for the occurrence of nanotechnology and related terms. A nanotechnology inclusion in curriculum (NIC) index was developed and used to rank each insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…NIC was proposed as a potential tool for the inclusion of nanotechnology in distinct educational programs. 20 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…NIC was proposed as a potential tool for the inclusion of nanotechnology in distinct educational programs. 20 …”
Section: Resultsmentioning
confidence: 99%
“…Multiple cross-sectional studies have shown that students enrolled in undergraduate and postgraduate programs in pharmacy, medicine, and biology, although they are conscious of the importance and relevance of nanotechnology or/and nanomedicine, have little exposure to it in their educational programs. 11,[17][18][19][20] The common finding is that no matter the major or the educational area, an important percentage of the students have a poor understanding of nanotechnology, their attitude is positive toward it, and most of them believed that they need more training and education in this field. The need for a curriculum change, which includes courses dedicated to teaching nanotechnology and its applications and reflects an interdisciplinary nature, was a common finding too.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a relative dearth of information regarding the rate and extent to which programs cover the medical application of nanotechnology in current pharmacy and pharmaceutical sciences curricula. An evaluation of the inclusion of nanotechnology in Master of Pharmaceutical Sciences programs in Portugal collected the curricula delivered at five public and four private Universities [30]. Curricula were systematically searched for references to nanotechnology or related terms (e.g., liposome, nano, colloid).…”
Section: Nanomedicine Coverage In Pharmacy Educationmentioning
confidence: 99%
“…Accordingly, European universities composed nanotechnology courses, researchers published articles on NST education, digital education sources were developed such as nanoyou. In the meantime, nano education outreach programs (Moraes, 2012;Saidi & Sigauke, 2017), integrating nanotechnology in the science curriculum (Blonder & Sakhnini, 2017;Neves, 2018;Yu & Jen, 2020), developing hands-on activities (Bagaria et al, 2011;Furlan, 2009;Lati et al, 2019), determining public understanding, awareness or attitudes towards NST (Scheufele & Lewenstein, 2005;Senocak, 2014;Vandermoere et al, 2011), instrument development (Lin et al, 2013;Schönborn et al, 2015) research studies were implemented.…”
Section: Introductionmentioning
confidence: 99%